Respuesta :

Answer:

y = 1/6 x^2 + 8/3 x + 49/6

Step-by-step explanation:

This is a parabola which opens upwards.

The distance of a point (x, y)  from the focus is

√[(x -  -8)^2  + (y - -1)^2] and

the distance of the point from the line y = -4

= y - -4

These distances are equal for a parabola so:

√[(x -  -8)^2  + (y - -1)^2] = y + 4

Squaring both sides:

(x + 8)^2 + (y + 1)^2  = (y + 4)^2

x^2 + 16x + 64 + y^2 + 2y + 1 = y^2 + 8y + 16

x^2 + 16x + 64 + 1 - 16 = 8y - 2y

6y = x^2 + 16x + 49

y = 1/6 x^2 + 8/3 x + 49/6 is the equation of the parabola.

Answer:

1/6(x+8)^2-5/2

Step-by-step explanation:

khan academy

plug into equation:

y=1/2(b-k) (x-a)^2 +1/2 (b+k)

y=1/2(-1--4) (x--8)^2 +1/2 (-1+-4)

y=1/6 (x+8)^2-5/2